Penyelesaian Sengketa Transaksi Tanah Adat - Bandu, Sri Jekan Anggun; Tjoanda, Merry; Uktolseja, Novyta (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
This study discusses the legitimacy of customary land transactions, land ownership by conducting land transactions, the emergence of disputes from customary land transactions, and the process of resolving disputes over customary land transactions through litigation and non-litigation channels. Purposes of the Research: To find out the legitimacy of customary land transactions and find out about the dispute resolution process of customary land transactions. This study uses the Normative Law research method which is carried out by examining legal materials related to the problems being studied, using statutory and conceptual approaches, and using primary and secondary data and analyzed descriptively. Results of the Research: Basically transactions are made individually, the transaction still may not conflict with normative provisions that exist in society (requirements for the validity of the agreement/transaction; legal reasons). Because it cannot be separated from society, transactions in customary law can only be said to be valid if individual interests are balanced with the interests of society. In the process of resolving customary land transaction disputes, litigation and non-litigation can be carried out. Settlement of disputes over customary land through litigation as a settlement of disputes between parties which is carried out through examinations before judges in court institutions, in the development of the times the community's need for justice and prosperity is getting bigger. So the settlement of disputes through litigation or courts is gradually felt to be less effective, the settlement of land disputes through litigation is felt to take too long and costs quite a lot. This situation causes justice seekers to look for other alternatives, namely by resolving disputes outside the formal court process, an alternative known as dispute resolution through non-litigation channels.